The impact of European policies on international collaboration in scientific investigation in Portugal and the United Kingdom - Sampaio Loio, Duarte (1996)
The Portuguese Electric Oven Company (CPFE), founded in 1917 in Portugal, initially directed its activity to the electrochemical industry. It produced calcium carbonate, using surplus energy from hydroelectric power stations in the serra da Estrela. From 1946 onwards, it started to make a wide range of metal alloys (ferrosilicon, ferromanganese, silicon manganese, and silicon metal). In parallel with the calcium carbonate industry, and derived from it, the CPFE developed a calcium cyanamide industry. The CPFE factory complex at Canas de Senhorim occupied about 200,000 square metres of land, and there were buildings on more than 20,000 square metres of that area. The CPFE was dependant on foreign sources for both financial and human resources. Until 1932, the firms Mines de Borralha and Rochette Frères nominated administrators to the management of the CPFE.